2018
DOI: 10.3748/wjg.v24.i37.4291
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral lipiodol embolism related to a vascular lake during chemoembolization in hepatocellular carcinoma: A case report and review of the literature

Abstract: A male patient underwent conventional transcatheter chemoembolization for advanced recurrent hepatocellular carcinoma (HCC). Even after the injection of 7 mL of lipiodol followed by gelatin sponge particles, the flow of feeding arteries did not slow down. A repeat angiography revealed a newly developed vascular lake draining into systemic veins; however, embolization was continued without taking noticing of the vascular lake. The patient’s level of consciousness deteriorated immediately after the procedure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Other authors reported cases of lipiodol-associated embolic stroke following TACE. 3 4 Lipiodol can penetrate through the tumor into the hepatic veins and cause stroke in patients with right-to-left shunt. In our case, the DEB-TACE and the PVA particles were more than 75 µg, with a very low likelihood of penetration into the hepatic veins given the lack of discernable intratumoral shunts; unless there was an undetectable one, which has an incidence of 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported cases of lipiodol-associated embolic stroke following TACE. 3 4 Lipiodol can penetrate through the tumor into the hepatic veins and cause stroke in patients with right-to-left shunt. In our case, the DEB-TACE and the PVA particles were more than 75 µg, with a very low likelihood of penetration into the hepatic veins given the lack of discernable intratumoral shunts; unless there was an undetectable one, which has an incidence of 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…TACE treatment in patients with HCC complicated by an AHVS may increase the post-treatment risk of pulmonary embolism, pulmonary infarction, and even cerebral embolism. 24 Furthermore, the histologic toxicity of the chemotherapy drugs may aggravate lung symptoms, such as pulmonary edema, atelectasis, blood pneumothorax, and even respiratory arrest. 25 Therefore, traditional TACE is not ideally appropriate and may even be dangerous for patients with AHVS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is noteworthy that regardless of whether the chemotherapeutic drugs used in TACE can induce or co-induce lung injury, 13 - 15 the suspension formed by the iodinated oil and chemical drugs may cause disruptions on the direct or indirect immune response to lung tissues, including diffused alveolar damage, non-cardiogenic pulmonary edema, vasculitis alveolar hemorrhage, ARDS, and allergic reaction alveolitis. The combination of 2 chemotherapy drugs and iodinated oil in TACE in this group of patients may increase the chemotherapy drug-related pneumonia.…”
Section: Discussionmentioning
confidence: 99%